Assessing Transformational Leadership In Islamic Education For Strengthening Religious Moderation In Madrasahs And Islamic Education - Nur Efendi (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study investigates the role of transformational leadership in strengthening religious moderation within Islamic educational institutions, focusing on SMK Islam Sunan Kalijaga Tulungagung. The study addresses leadership practices, implementation of moderation values, and their impact on students and institutional development. A qualitative descriptive design was employed using in-depth interviews, observations, and document analysis involving school leaders, teachers, and students. Data were analyzed through condensation, display, and interpretation supported by triangulation to ensure credibility. The findings show that transformational leadership is enacted through value-driven vision, exemplary behavior, and participatory engagement that shape institutional culture and learning practices. Moderation values are embedded across curriculum, extracurricular activities, and daily interactions, creating a consistent environment of tolerance and inclusivity. Students demonstrate increased openness, critical awareness, and respectful communication in diverse contexts. Institutional development reflects sustainability through continuous program innovation and stakeholder collaboration. The study concludes that transformational leadership strengthens religious moderation by integrating ethical guidance, policy alignment, and pedagogical practices within Islamic education.